Professional Orientation as a Factor of Sustainable Development of Future Socionomic Specialists: Research Results and Methodological Recommendations - VASYLENKO, Olena; OSTROVSKA, Nataliia; PODLEVSKA, Nelia; SOMKINA, Inna; OTROSHCHENKO, Nataliia; DUVANSKA, Kateryna; LYTVYNOVA, Nataliia (European Journal of Sustainable Development, 2025)
The article addresses the issue of professional orientation as a factor in the sustainable development of future specialists in the socionomic field. It has been established that an individual’s professional orientation is an integrated concept that encompasses both general orientation and the associated motivational sphere, which shapes a selective attitude toward a particular profession, a desire to apply one's knowledge, experience, and abilities within it, and to achieve self-realization through it. This implies the study of professional orientation as a factor in the sustainable development of future specialists in the socionomic sphere. The results of the diagnostics concerning the peculiarities of professional orientation development among future socionomic specialists revealed that the respondents demonstrate a well-developed professional identity, possess clear life plans, and have a consciously defined professional goal. The students demonstrate a high level of self-perception, with the most important values including a happy family life, health, happiness of loved ones, a materially secure life, independence, and responsibility. However, a certain portion of the respondents exhibited moderate and low levels of achievement motivation development. Based on these findings, methodological recommendations have been developed and substantiated for academic and teaching staff to foster professional orientation among students of socionomic specialties. Keywords: future socionomic specialists; orientation; professional orientation; professional activity